Total UK multi-centre experience with a novel arterial occlusion device (Duct Occlud pfm). Issue 6 (December 1996) - Tometzki, A.; Chan, K.; De Giovanni, J.; Houston, A.; Martin, R.; Redel, D.; Redington, A.; Rigby, M.; Wright, J.; Wilson, N.
Abstract : OBJECTIVE: To report the total UK multicentre experience of a novel arterial occlusion device (Duct Occlud pfm). DESIGN: Descriptive study of selected non-randomised paediatric patients with a variety of aortopulmonary connections. SETTING: Five UK tertiary referral centres for congenital heart disease. PATIENTS AND METHODS: Between March 1994 and February 1995, 57 children aged 2 weeks to 14 years (median 50 months) underwent attempted closure of their aortopulmonary connection. Fifty one had persistent arterial ducts and 9 of them had had a Rashkind umbrella device implanted. Five patients had superfluous modified Blalock-Taussig shunts (mBTS). In one there was also a native major aortopulmonary collateral artery (MAPCA). Another patient had a native major aortopulmonary connection (APC). Transcatheter occlusion was attempted in all cases through a 4 F delivery catheter. RESULTS: Devices were successfully deployed in 49/57 (86%) patients. Seven of 51 cases with persistent arterial ducts were judged too large for the device and a Rashkind umbrella was used. 40 (91%) of the 44 in whom the detachable coil device was used had complete occlusion at 24 hours on colour flow Doppler echocardiography. Devices were successfully deployed in all 6 remaining patients (4 mBTS, 1 mBTS + MAPCA, and 1 APC). Embolisation of a device occurred on 4 occasions. Two devices were not retrieved but caused no apparent clinical problems. CONCLUSION: This novel detachable coil type occlusion system compares favourably with other methods of transcatheter occlusion of native, residual, or surgically created aortopulmonary shunts. The delivery system allows its use in small children.